(untitled) (Journal of actual problems of jurisprudence, 2019)
The article deals with the content and essence, guarantee the rule of the Constitution, examines the need to improve the consistent constitutional control in the Republic of Kazakhstan, the analysis of the need to eliminate the contradictions in the study of problems of rule of the Constitution.